Komunikasi Interpersonal dalam Mengurangi Ketergantungan Alkohol di Kalangan Remaja di Desa Lalang, Kecamatan Rana Mese Kabupaten Manggarai Timur - Erniwati Erniwati; Nurafny Shahnyb; Yustina Mega Baru (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Interpersonal communication is a crucial aspect of human life, both within the family and in the community, as it serves as a means of providing motivation, support, and positive guidance. One social issue of considerable concern is alcohol dependence among adolescents, which can negatively impact their physical, mental, and social development. This study was conducted to determine how interpersonal communication between parents and adolescents in Lalang Village, Rana Mese District, East Manggarai Regency, plays a role in reducing alcohol dependence. Furthermore, this study also examined the strategies parents use to overcome barriers to interpersonal communication in an effort to prevent alcohol consumption among adolescents. This study used a qualitative method with a descriptive approach. Data were obtained through in-depth interviews, observations, and documentation of parents and adolescents in Lalang Village. Analysis was conducted by examining the communication patterns that occur, the obstacles encountered, and their impact on adolescent behavior related to alcohol consumption. The results of the study indicate that interpersonal communication between parents and adolescents in reducing alcohol dependence is still not optimal. This is evident in the lack of time spent together between parents and adolescents, the low response of adolescents to messages delivered face-to-face, and the lack of understanding on the negative impacts of alcohol on health on both parties. Cultural factors and limited knowledge also hinder the effectiveness of interpersonal communication. In conclusion, effective interpersonal communication is essential for educating and guiding adolescents to reduce alcohol consumption. Efforts should include improving parental communication skills, strengthening family interactions, and raising public awareness of the dangers of alcohol. Educators and community leaders also play a crucial role in supporting the education process and preventing alcohol dependence among adolescents.